2018
DOI: 10.1186/s13756-018-0404-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of multidrug-resistant gram-negative bacteria infections in intensive care unit from Nepal- a prospective cohort study

Abstract: BackgroundInfections caused by multi-drug resistant gram-negative bacterial infections are the principle threats to the critically ill patients of intensive care units. Increasing reports of these infections from the Nepalese intensive care unit underline the clinical importance of these pathogens. However, the impact of these infections on the patient’s clinical outcome has not yet been clearly evaluated. The objective of our study was to determine the incidence and associated clinical outcome of multi-drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 25 publications
(47 reference statements)
4
34
3
2
Order By: Relevance
“…[21][22][23] Other studies involving ICU patients revealed either lower or similar rates of drug resistance among the GNB compared to the current study. 24,25 A study on 137 patients in Nepal reported 46% of the GNB isolates obtained from an ICU to cause MDR infections. 24 Another study in India, which looked at the bacterial isolates in critically ill patients with ventilator-associated pneumonia, found that 88% of the isolates were GNB, of which 72% were responsible for MDR infections.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Other studies involving ICU patients revealed either lower or similar rates of drug resistance among the GNB compared to the current study. 24,25 A study on 137 patients in Nepal reported 46% of the GNB isolates obtained from an ICU to cause MDR infections. 24 Another study in India, which looked at the bacterial isolates in critically ill patients with ventilator-associated pneumonia, found that 88% of the isolates were GNB, of which 72% were responsible for MDR infections.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, ABR has gained global attention due to the increasing incidence of multidrug-resistant (MDR) organisms causing treatment failures, antibiotic residues in food, and the public health risks it poses [ 3 ]. There is an increase in the incidence and dissemination of MDR organisms in humans, health facilities, animals, foods, and the environment [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the increase of hospital stays, readmissions, additional use of antimicrobials, and treatment failure was expected for patients infected by MDR strains [11]. The rapid rise of MDR Gram-negative bacteria (GNB) is of particular concern since higher mortality risk of nosocomial infections caused by MDR vs. non-MDR GNBs was noted [12,13].…”
Section: Introductionmentioning
confidence: 99%